Meningkatkan Publikasi Ilmiah Mahasiswa Program Studi Pendidikan Fisika Melalui Edukasi Penulisan Artikel Di FKIP Universitas Mataram - Amrullah, Lalu Azikri; Alia Cahyani; Gaisya Rahma Putri; Handrianto (Journal of Science Technology and Education, 2025)
This article discusses the implementation of a scientific article writing workshop organized by the Physics Education Study Program Student Association (Himafis) at the FKIP, University of Mataram in 2024. This activity aims to improve the writing skills of students, alumni, and lecturers in compiling quality scientific articles. This workshop consists of several stages, including preparation, implementation, and discussion. In the preparation stage, a committee was formed from students and coordinated with the association's supervisor to plan online and offline activities. The workshop was attended by 48 participants and presented competent speakers, including professors and alumni of the study program. The material presented included an introduction to scientific articles, article structure analysis, and tips and tricks in writing. The interactive discussion between participants and speakers showed high enthusiasm, indicating the need for further training in scientific writing. The results of this activity are expected to increase the productivity of scientific paper publications among students, as well as overcome the challenges faced in writing scientific articles.